Manufacturing technology, optical and spectral properties of nano-structurized thin ZnO films - Panasyuk, M.R.; Turko, B.I.; Kapustianik, V.B.; Lubochkova, G.A.; Rudyk, V.P.; Vas`kiv, A.P.; Davydov, V.M. (Functional Materials, 2005)
Dependence of cathodoluminescence parameters on the annealing temperature and RF ion etching has been studied for nano-structurized thin zinc oxide films obtained by RF magnetron reactive sputtering. The film structure has been characterized by X-ray diffraction. Thermal annealing and RF ion etching have been found to increase the cathodoluminescence intensity, mainly due to enlargement of the nanocrystallite mean size.